2019
DOI: 10.32383/appdr/112187
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD-ESI/MS Analysis of Arnica TM Constituents

Abstract: The herbal drugs obtained from Arnica montana flowers are known for their anti-inflammatory activity. However, there is no detailed data on chemical constituents of the whole Arnica plant. HPLC-DAD-ESI/MS analysis of the whole Arnica montana plant (Arnica TM), used in the preparation of allopathic and homeopathic medicinal products, has been conducted. The qualitative and quantitative analysis comprised phenolic acids, flavonoids and sesquiterpene lactones ñ helenalin and dihydrohelenalin esters identified ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This ratio ranges from 1.3 for a thymol derivative to 3.1 for 4-hydroxy-8-sphingenine. Concerning the annotation of quinic acid (QA), fumaric acid, 1,5-dicaffeoyl-and 3,5dicaffeoyl quinic acids (DCQA), they have previously been described in A. montana [7,16,17] and their MS/MS fragmentations support the proposed structures. To distinguish the 6 (1,3-1,4-1,5-3,4-3,5 or 4,5) DCQA regioisomers identified in A. montana, Lin and Harnly [16] established a method based on their elution order under various LC conditions.…”
Section: Dereplication Of Discriminating Compoundsmentioning
confidence: 85%
See 1 more Smart Citation
“…This ratio ranges from 1.3 for a thymol derivative to 3.1 for 4-hydroxy-8-sphingenine. Concerning the annotation of quinic acid (QA), fumaric acid, 1,5-dicaffeoyl-and 3,5dicaffeoyl quinic acids (DCQA), they have previously been described in A. montana [7,16,17] and their MS/MS fragmentations support the proposed structures. To distinguish the 6 (1,3-1,4-1,5-3,4-3,5 or 4,5) DCQA regioisomers identified in A. montana, Lin and Harnly [16] established a method based on their elution order under various LC conditions.…”
Section: Dereplication Of Discriminating Compoundsmentioning
confidence: 85%
“…It grows in the wild across Europe in meadows, pastures and heaths, mainly in the mountains, from south Norway and Latvia to south Portugal, the North Apennines and South Carpathians [1][2][3]. Arnica flowers have been known for centuries as an herbal remedy, originally being used internally in phytotherapy, and currently only applied externally on injuries, such as bruises, sprains, inflammation caused by insect bites, gingivitis, aphthous ulcers and the symptomatic treatment of rheumatic muscle and joint complaints [4][5][6][7]. A. montana also has a very long history with regard to its homeopathic utilization since it was originally described by Samuel Hahnemann, the inventor of this form of therapy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin 3-O-glucuronic acid and kaempferol-3-O-glucoside were the dominant flavonoids, but quercetin 3-O-β-D-glucoside, patuletin 3-O-β-D-glucoside, kaempferol 3-O-β-D-glucuronide, 6-methoxykaempferol 3-O-β-D-glucoside, hispidulin, kaempferol, quercetin, apigenin, and rutine were also found. Protocatechuic and 3,5-dicaffeoylquinic acid were the major phenolic acids, but chlorogenic, caffeic, 1-methoxy-oxaloyl-3,5-dicaffeoylquinic acid, and 4,5-dicaffeoylquinic acid were also present [ 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The acetone exudates of flower heads were richer in surface flavonoids than leaf extracts and presented high contents of the flavonoids 6-OH luteolin 6-methyl ether and kaempferol-6-methyl ether.…”
Section: Introductionmentioning
confidence: 99%
“…Although the main anti-inflammatory and analgesic activity of arnica is due to the sesquiterpene lactones helenalin and 11, 13-dihydrohelenalinester, the flavonoid and phenolic fractions could also be of interest because their additional antioxidant and antimicrobial effects could act synergistically with sesquiterpene lactones [ 7 , 12 , 14 ]. Other authors have reported that a methanol extract alleviated arthritis in rats with better therapeutic efficacy than dexamethasone, and this action was probably due to the combined action of phenolic and flavonoid compounds [ 3 ].…”
Section: Introductionmentioning
confidence: 99%